BIM (Building Information Modeling) based collaborative design and construction process optimization - Ke, Dandan (Applied mathematics and nonlinear sciences, 2024)
BIM technology is an important method to solve the problem of collaborative design and construction processes in the construction process of engineering projects. Based on BIM, this paper proposes a corresponding optimization model from the perspective of collaborative design and construction processes, respectively. In the collaborative design optimization model, the engineering collaborative management theory is utilized to extract indicators of schedule, cost, and quality to establish an IFC-based collaborative design optimization model. A multi-objective genetic algorithm is employed to solve the construction process optimization model by establishing the optimal scheduling model with schedule and cost minimization objectives. As instance, a second-class residential land use project in Chaoyang District, Beijing, is the subject of collaborative design and construction process optimization analysis. The optimization rate of the crossbeam floor cover solution compared with the slab floor cover solution without secondary beams is 13.5%, and the optimization effect of the co-design process is evaluated at 81.48 points, which reaches the standard of “good”. During the construction of the 6# building, the shortest duration of wall panel construction is 0.8416d, and the duration practice is shortened by 0.1467d. The overall construction quality score is 81.126, which reaches the level of “good”.